Introduction to engineering design : modelling, synthesis and problem solving strategies - Samuel, A. E. (Andrew E.), 1931- (Butterworth-Heinemann, 1999)
Introduction to Engineering Design is a completely novel text covering the basic elements of engineering design for structural integrity. Some of the most important concepts that students must grasp are those relating to 'design thinking' and reasoning, and not just those that relate to simple theoretical and analytical approaches. This is what will enable them to get to grips with *practical* design problems, and the starting point is thinking about problems in a 'deconstructionist' sense. By analysing design problems as sophisticated systems made up of simpler constituents, and evolving a solution from known experience of such building blocks, it is possible to develop an approach that will enable the student to tackle even completely alien design scenarios with confidence. The other essential aspect of the design process - the concept of failure, and its avoidance - is also examined in detail, and the importance not only of contemplating expected failure conditions at the design stage but also checking those conditions as they apply to the completed design is stressed. These facets in combination offer a systematic method of considering the design process and one that will undoubtedly find favour with many students, teaching staff and practising engineers alike.